ANALISIS PERAN ORANG TUA DALAM MENERAPKAN PENDIDIKAN KARAKTER ANAK DI ERA REVOLUSI INDUSTRI 4.0 (STUDI KASUS GURU BERKELUARGA DI PP. AL-AMIEN PRENDUAN) - Rosyidatul Munayah (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
This study discusses how family teachers at TMI and MTA Al-Amien Prenduan Islamic Boarding Schools apply character education to children, as well as what are the obstacles and supporting factors in it, especially in the era of the industrial revolution 4.0 (millennial era). The approach used in this study uses a qualitative approach. The results of this study can show that the role of parents in educating their children's character cannot be separated from the parenting applied by each parent with various kinds of sophisticated technology. Besides being able to assist the process of implementing character education, it also requires parents to carry out supervision and extra education. They apply character education to children in various educational methods, based on Islamic guidance.